Phytochemical analysis and docking study of compounds present in a polyherbal preparation used in the treatment of dermatophytosis - Nagesh Simhadri; Muthuchamy Muniappan; Iyanar Kannan; Subramanyam Viswanathan (Mazandaran University of Medical Sciences, 2017)
Background and Purpose: Soleshine is a polyherbal preparation established in the market for the treatment of cracks and tinea pedis, which is applied externally. This preparation is composed of the extracts of indigenous plants, namely Azadirachta indica, Lawsonia alba, and Shorea robusta, mixed with castor oil and sesame oil. In the present study, an attempt was made to identify the constituents of soleshine and identify some potential drug-like molecules that can inhibit important drug targets of the dermatophytes using molecular docking method. Materials and Methods: The active ingredients of polyherbal preparation were identified with the aid of gas chromatography-mass spectrometry (GC-MS). Two major compounds were selected based on the retention time and percentage of the area covered in the graph for docking study. The three-dimensional structures of 1,3-β-glucan synthase, chitinase, fungalysin, and lumazine synthase were derived by homology modelling using MODELLER software, version 9.0. The docking of the ligand and receptor was performed using iGEMDOCK and AutodockVina software. The physicochemical properties, lipophilicity, hydrophilicity, and drug likeness properties were obtained from the Swiss ADME online server tool. Results: The GC-MS analysis demonstrated the presence of different phytochemical compounds in the extract of polyherbal preparation. A total of 20 compounds were identified, among which 3,7-dimethyl-2,6-octadienaland 2-pentene-2-methyl were the major compounds. Regarding 3,7-dimethyl-2,6-octadienal, the covered area and height were 40.15% and 46.17%, respectively. These values were 31.90% and 23.33% for 2- pentene-2-methyl, respectively. These two major compounds had an excellent binding affinity and obeyed the rules for the drug likeness and lead likeness. Conclusion: As the findings indicated, the two major ingredients present in soleshine showed a good antifungal activity as they inhibited the enzymes responsible for the survival of fungal organism; furthermore, they were appropriate for the lead molecules. Keywords: Anti-fungal activity, Chitinase, Dermatophytes, Fungalysin, Lumazine synthase, Molecular docking, Soleshine, 1,3-β-Glucan synthase